Niger's Infrastructure : A Continental Perspective - Dominguez-Torres, Carolina (2012)
Between 2000 and 2005 infrastructure made a net contribution of less than a third of a percentage point to the improved per capita growth performance of Niger, one of the lowest contributions in Sub-Saharan Africa. Raising the country's infrastructure endowment to that of the region s middle-income countries could boost annual growth in Niger by about 4.5 percentage points. Niger has made significant progress in some areas of its infrastructure, including water and telecommunications. But the country still faces a number of important infrastructure challenges, the most pressing of which is probably in the water and sanitation sector, as 82 percent of Nigeriens still practice open defecation, the highest in the continent. Niger also faces significant challenges in the power sector, as only 8 percent of the population is electrified. Niger currently spends about $225 million per year on infrastructure, leaving an annual funding gap of $460 million even after savings from curing inefficiencies are taken into account. Niger can close that gap by tapping alternative sources of financing or by adopting lower-cost technologies. There is plenty of room for private-sector participation in Niger's infrastructure sectors, and the adoption of lower-cost technologies could reduce the funding gap by almost half.